Chronology and documentary handbook of the State of Hawaii - Jennings, Helen (Dobbs Ferry, N.Y. ; Oceana Publications, 1978)
Includes a chronology of historical events in Hawaii, a biographical directory, the first state constitution, and other selected historical documents.
Includes bibliographical references and index.
Keywords: Hawaii -- History -- Chronology; Hawaii -- History -- Sources; Hawaii -- History